Complexities of collaborative product development - Bruce, Margaret (Technovation)
The complexity, shorter lead times and high costs of product development have lent momentum to collaborative ventures. So much so that part of the 'received wisdom' of information and communication technology (ICT) suppliers is that collaboration is the preferred route for product development. In this paper, it is argued that the alleged benefits of collaboration may not always be achieved in practice and consequently it is important to pay attention to managerial and other factors that may influence the outcome of collaborative product development.